2021
DOI: 10.3390/v13101960
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar-like Macrophages Attenuate Respiratory Syncytial Virus Infection

Abstract: Respiratory Syncytial Virus (RSV) is the leading cause of acute lower respiratory infections in young children and infection has been linked to the development of persistent lung disease in the form of wheezing and asthma. Despite substantial research efforts, there are no RSV vaccines currently available and an effective monoclonal antibody targeting the RSV fusion protein (palivizumab) is of limited general use given the associated expense. Therefore, the development of novel approaches to prevent RSV infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Importantly, macrophage polarization is also likely involved in RSV infection ( 66 , 67 ). Although there is evidence showing that alveolar macrophages necroptosis drives disease pathogenesis during RSV infection ( 68 ), there are also evidence indicating that AM can control/attenuate RSV pathology ( 44 , 68 71 ). Our study showed that OM–85 treatment used as preventive measure consistently maintained AM population in the lungs, while RSV–infected untreated animals presented a pronounced reduction in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, macrophage polarization is also likely involved in RSV infection ( 66 , 67 ). Although there is evidence showing that alveolar macrophages necroptosis drives disease pathogenesis during RSV infection ( 68 ), there are also evidence indicating that AM can control/attenuate RSV pathology ( 44 , 68 71 ). Our study showed that OM–85 treatment used as preventive measure consistently maintained AM population in the lungs, while RSV–infected untreated animals presented a pronounced reduction in these cells.…”
Section: Discussionmentioning
confidence: 99%
“… 17 and kill respiratory syncytial virus (RSV) and prevent RSV‐induced lung injury. 18 Here, we further characterized ALMs for their efficacy to treat bacterial lung infections. We evaluated the non‐pharmacological antimicrobial functions of ALMs, specifically for bacteria known to colonize the lungs of immune‐compromised individuals, such as P .…”
Section: Introductionmentioning
confidence: 99%
“…A . ) 17 and kill respiratory syncytial virus (RSV) and prevent RSV‐induced lung injury 18 . Here, we further characterized ALMs for their efficacy to treat bacterial lung infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the role of macrophages in RSV infection, in vivo models have typically been used that deplete alveolar macrophages, or adoptively transfer specific types of macrophages into the lungs again after depletion. However, there are conflicting findings in these reports, with some suggesting macrophages are protective [ 23 26 ], while others suggest they contribute to the pathology [ 27 , 28 ] of infection. To add to the complexity, modifying the phenotype of alveolar macrophage during infection may also provide a protective effect against viral infection [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%